2016
DOI: 10.18632/oncotarget.13869
|View full text |Cite
|
Sign up to set email alerts
|

Loss of expression of the recycling receptor, FcRn, promotes tumor cell growth by increasing albumin consumption

Abstract: Tumor cells rely on high concentrations of amino acids to support their growth and proliferation. Although increased macropinocytic uptake and lysosomal degradation of the most abundant serum protein, albumin, in Ras-transformed cells can meet these demands, it is not understood how the majority of tumor cells that express wild type Ras achieve this. In the current study we reveal that the neonatal Fc receptor, FcRn, regulates tumor cell proliferation through the ability to recycle its ligand, albumin. By cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 37 publications
0
38
1
1
Order By: Relevance
“…Lower serum ALB may indicate that an individual has lower FcRn levels, resulting in higher ALB CL by catabolism; likewise, an individual with lower FcRn levels might be expected to exhibit higher CL of any administered IgG mAb. Recent data from preclinical studies showed that loss of expression of the recycling receptor, FcRn, promotes tumour cell growth by increasing albumin consumption, which shows how FcRn and ALB can be correlated. However, if there is an association between FcRn levels and disease severity, it still remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Lower serum ALB may indicate that an individual has lower FcRn levels, resulting in higher ALB CL by catabolism; likewise, an individual with lower FcRn levels might be expected to exhibit higher CL of any administered IgG mAb. Recent data from preclinical studies showed that loss of expression of the recycling receptor, FcRn, promotes tumour cell growth by increasing albumin consumption, which shows how FcRn and ALB can be correlated. However, if there is an association between FcRn levels and disease severity, it still remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…An additional advantage of SPEDOX is cancer targeting, based on the hFcRn‐mediated HSA recycling mechanism. [ 21,35,36 ] If a cancer cell expresses less hFcRn than its normal counterpart, SPEDOX recycling would be less efficient, leading to increased endocytosis of SPEDOX into the cancer cell. DOX may be released from SPEDOX by different mechanisms, such as dissociation and HSA degradation, leading to higher free DOX concentration in the cancer cells.…”
Section: Figurementioning
confidence: 99%
“…Second, we reported FcRn mRNA and protein levels in both lung cancerous tissue and non-cancerous tissue associated with favorable prognosis in non-small cell lung cancer ( 13 ). Third, studies involving neoplastic cells expressing different levels of FcRn showed that FcRn-mediated recycling of albumin reduced tumor cell growth and proliferation ( 14 ).…”
Section: Introductionmentioning
confidence: 99%